(untitled) - Grassi, Carlos J.; Chambouleyron, Jorge Luis (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Influencia de la altura del cultivo en la evapotranspiración relativa de la alfalfa (1965)

(untitled)
Report herein are be results of an experiment rneasuring tbe influence of crop heigh t on the relative evapotranspiration of alfalfa field. Experiments were conducted at the Instituto de Suelos y Riego Experimental Farm, Facultad de Ciencias Agrarias, Mendoza, Argentina. Three different treatments of crop height were evaluated : treatment A, complete plant height development (before cutting); treatment B, half height plant development; treatment C, small-plant height (after cutting). Total evapotranspiration of the cyele and rate of evapotranspiration were higher in B than in treatment C. Average evapotranspiration values were : 4, 4.90 mm per day ; B, 3.86 mm per day ; and C, 3.17 mm per day. The evapotranspiration evaporation ratios in each treatment were: A, 1.06; B, 0.83; e, o.867. The reported experiments show that even in a perennial crop like alfalfa, which completely covers the soil, a considerable difierence in the relative evapotranspiration value is obtained. From the period after cuttiug to the period of full leaf and complete plant height development the crop coefficient is rising. This variation of crop coefficients shold be kept in mind in applying formulas to estimate the evapotranspiration rate of an alfalfa crop for specific periods between cuttings.